Original paperCARDIORESPIRATORY FITNESS, ACTIVITY LEVEL, HEALTH-RELATED ANTHROPOMETRIC VARIABLES, SEDENTARY BEHAVIOUR AND SOCIOECONOMIC STATUS IN A SAMPLE OF IRANIAN 7-11 YEAR OLD BOYS - Esmaeilzadeh, S.; Kalantari, H.; Nakhostin-Roohi, B. (Biology of Sport, 2013)
The purpose of this study was to evaluate cardiorespiratory fitness (CRF), activity level, some health- related anthropometric variables, sedentary behaviour and socioeconomic status (SES) of 7-11 year old boys in the city of Ardabil, Iran. Of 21 253 school boys aged 7-11 years, 766 participated in this study using the cluster · sampling method. Subjects underwent standard anthropometry. One-mile test was used to evaluate VO2max. BMI cut-off points were used to identify weight status. Child’s TV watching and video playing daily time (TVVPT) was taken for sedentary behaviour evaluation. SES and activity level were measured by standard questionnaires. Of all participants, 8.9% (N=68) of students had CRF lower than normal and 58.6% (N=449) of them had · inadequate physical activity. There was a significant adverse relationship between VO2max and body mass index (BMI), waist to height ratio (WHtR), waist circumference (WC), and fat mass (FM) (p<0.05). A significant direct association between SES and both FM and TVVPT was observed (p<0.05). Significantly lower physical · activity and VO2max, and higher TVVPT were observed in the obese boys than their counterparts (p<0.05). The results of this study indicated a significant relationship between CRF and physical activity, and health-related anthropometric variables in a selected sample of 7-11 year boys. Moreover, the obese subjects had not only lower physical activity but also longer sedentary behaviour time than their counterparts.